Construction of BiVO4 microspheres sensitized TiO2 NTAs for the enhanced photocatalytic mineralization of organic dyes. Issue 9 (15th June 2020) - Zhang, Han; Li, Yanmin; Wu, Yue; Wang, Yujie; Lin, Zhipeng; Cao, Dandan; Wang, Qingyao
Abstract: In the present work, BiVO4 microspheres were deposited on TiO2 NTAs via the solvothermal method using urea as the mineralizer. The binary heterojunction formation significantly enhanced the solar response region and intensity, and the electron transfer path was built at the interface of two semiconductors, which was the main reason for the enhanced photoelectrochemical and photocatalytic performances. The S-2 electrode prepared with urea concentration of 2 mol/L displayed the high visible light photocurrent of 73.76 μA/cm 2 and photovoltage of −0.30 V. Furthermore, the S-2 photocatalyst also showed excellent photocatalytic decoloration ability of MO, RhB and MB dyes, and the corresponding decomposition efficiencies were 55.82%, 41.62% and 89.90% under solar irradiation. Except for the organic dyes, Cr(VI) ions also could be reduced into Cr(III), and the photocatalytic efficiency achieved 74.05% after 3 h solar irradiation. The active group and photocatalytic mechanism were proposed to illuminate the essential reason. The experimental results indicated that the novel BiVO4 /TiO2 NTAs with binary heterojunction are attractive photocatalysts for the dyeing and printing water treatment.